2016
DOI: 10.1051/epjconf/201610802016
|View full text |Cite
|
Sign up to set email alerts
|

GPU-Accelerated Population Annealing Algorithm: Frustrated Ising Antiferromagnet on the Stacked Triangular Lattice

Abstract: Abstract. The population annealing algorithm is a novel approach to study systems with rough free-energy landscapes, such as spin glasses. It combines the power of simulated annealing, Boltzmann weighted differential reproduction and sequential Monte Carlo process to bring the population of replicas to the equilibrium even in the low-temperature region. Moreover, it provides a very good estimate of the free energy. The fact that population annealing algorithm is performed over a large number of replicas with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The new algorithm introduced here, which we call EPA, is not based on Markov chains but on the sequential Monte Carlo method. PA was first studied in [53,54] and more recently developed further in [55][56][57][58][59][60][61]. It is based on the initialization of a population of replicas drawn from the equilibrium distribution at high temperatures, which is then subsequently cooled to lower and lower temperatures.…”
Section: Entropic Population Annealingmentioning
confidence: 99%
“…The new algorithm introduced here, which we call EPA, is not based on Markov chains but on the sequential Monte Carlo method. PA was first studied in [53,54] and more recently developed further in [55][56][57][58][59][60][61]. It is based on the initialization of a population of replicas drawn from the equilibrium distribution at high temperatures, which is then subsequently cooled to lower and lower temperatures.…”
Section: Entropic Population Annealingmentioning
confidence: 99%
“…PAMC, on the other hand, remains a relatively new simulation method. Although careful systematic studies of PAMC [16,18] exist, and the method has been applied broadly [9,[19][20][21], little effort has been made to thoroughly optimize the algorithm. Here we focus on this problem and study various approaches to improve the efficiency of PAMC for large-scale simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Note that PAMC implemented on graphics processing units has been discussed extensively in Refs. [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested another phase transition occurring at lower temperatures a to a ferrimagnetic phase (M, −M/2, −M/2), with one sublattice fully ordered and two partially disordered [10,12,21]. On the other hand, several other studies argued that due to linear-chain-like excitations in the system there is a crossover to the low-temperature phase, which is a 3D analog of the 2D Wannier phase [9,13,14,26,27]. In the IATL to SIATL dimensional crossover study it was found that the PD phase can also develop in the system consisting of a sufficiently large but finite number of the IATL layers stacked along the z axis.…”
Section: Introductionmentioning
confidence: 99%